2006
DOI: 10.1021/ma061215h
|View full text |Cite
|
Sign up to set email alerts
|

Addition-Type Polynorbornenes with Si(CH3)3 Side Groups:  Synthesis, Gas Permeability, and Free Volume

Abstract: Polymerization of norbornene bearing Si(CH3)3 groups in the 5-position with the opening of double bonds and its copolymerization with 5-(n-hexyl)norbornene were realized in the presence of nickel(II) naphthenate/methylaluminoxane catalyst system. The completely saturated homopolymer containing Si(CH3)3 group (APNSi) and a copolymer containing both Si(CH3)3 and n-hexyl side groups (ACPNHSi) were prepared. The polymers have molecular mass of about 300 000 and a high glass transition temperature (T g > 340 °C). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
90
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 52 publications
9
90
1
Order By: Relevance
“…As was shown in the earlier studies, for PTMSP, P(O 2 ) decreases by an order of magnitude after heating at 100°C for 15 h [31] and by two orders of magnitude after heating at 120°C for 8 h [32]. At the same time, oxygen permeability of the addition Poly[5-(TriMethylSilyl)Norborn-7-ene] (PTMSN) decreases only from 980 to 900 Barrer after annealing in air at 80°C for 16 h [33].…”
Section: Thermal Resistancesupporting
confidence: 65%
“…As was shown in the earlier studies, for PTMSP, P(O 2 ) decreases by an order of magnitude after heating at 100°C for 15 h [31] and by two orders of magnitude after heating at 120°C for 8 h [32]. At the same time, oxygen permeability of the addition Poly[5-(TriMethylSilyl)Norborn-7-ene] (PTMSN) decreases only from 980 to 900 Barrer after annealing in air at 80°C for 16 h [33].…”
Section: Thermal Resistancesupporting
confidence: 65%
“…It has been reported that the introduction of SiMe 3 group in poly(norbornene) results in a significant increase in a gas permeability, 12,18 and as a results of WAXD and PALS analysis, it was concluded that such behavior was ascribed to an increase in the free volume. Furthermore, the effect of the substituent on gas permeability was much stronger for addition-type poly(norbornene), compared to ROMP-type, relating to the rigidity of the backbone.…”
Section: Gas Permeation Properties Of Poly(norbornene) With Siloxane mentioning
confidence: 98%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Heitz et al 2,3 investigated the addition-type copolymerizations of norbornene with norbornene carboxylic acid esters, and found that the solubility of the copolymers and the thermal properties, such as glasstransition and decomposition temperatures, were dependent on the content as well as structure of the substituents. Risse et al [4][5][6] came to the same conclusion by studying poly-(norbornene)s containing hydroxyl, carboxylic acid and ester.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of very stiff and highly permeable material is the recently discovered addition type polynorbornene with Si(CH3)3 substituents 15) . This glassy polymer (Tg > 350 ℃)…”
Section: Yampolskii: Some Trends In Materials Science Of Membranes Fomentioning
confidence: 99%